Monitoring of atropine anticholinergic drug using voltammetric sensor amplified with NiO@Pt/SWCNTs and ionic liquid. (February 2022) - Tavana, Toktam; Rezvani, Ali Reza
Abstract: In this work, the synergic impact of 1-ethyl-3-methylimidazolium methyl sulfate (EMMS) and NiO doped Pt decorated SWCNTs (NiO@Pt/SWCNTs) in carbon paste matrix was examined as an analytical tool for investigating electrochemical behavior of atropine. The voltammetric results revealed that NiO@Pt/SWCNTs/EMMS/CPE exhibited an excellent electrocatalytic activity towards redox reaction of atropine in aqueous solution pH = 10.0. The NiO@Pt/SWCNTs/EMMS/CPE offered the best electro-analytical conditions for monitoring of atropine in the concentration range of 4.0 nM–220 μM with an increase in oxidation current about 5.93 times. On the other hand, NiO@Pt/SWCNTs/EMMS/CPE displayed a long time stability (about 60 days) for monitoring of atropine. The ability of NiO@Pt/SWCNTs/EMMS/CPE as an electroanalytical tool for monitoring of atropine was investigated, and the recovery range was detected as to be 97.6%–104.25% for this goal. Graphical abstract: Image 1 Highlights: Monitoring of atropine anticholinergic drug. Electrochemical sensing of Atropine in drug samples in nanomolar level. Introducing of NiO@Pt/SWCNTs and 1-Ethyl-3-methylimidazolium methyl sulfate as two conductive mediators.